2019
DOI: 10.4236/ojce.2019.94020
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Cost Advantages of Using Polyethylene Terephthalate Fibre Reinforced Concrete with Fly Ash as a Partial Cement Replacement

Abstract: Solid waste disposal is an alarming problem in most African countries. Plastic wastes like Polyethylene Terephthalate (PET) bottles and powdered wastes like fly ash are severely persisting environmental hazards. They are brutally polluting the water bodies, landfills, as well as the atmosphere. The construction industry has been working towards improving concrete quality by developing alternative methods like partial cement replacement with different pozzolanic elements as well as using waste fibrous materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…The mixture containing 15% had the lowest flexural strength at all fibre percentages due to the lower workability in comparison to the mixtures containing higher fly ash content. This trend agrees with study by Singh et al (2020) [22] and Kassa et al (2019) [37] who reported a higher flexural strength at high fly ash content and low fibre reinforcement content.…”
Section: Effect Of Pet Fibre and Fly Ash On Composite Flexural Strengthsupporting
confidence: 93%
See 1 more Smart Citation
“…The mixture containing 15% had the lowest flexural strength at all fibre percentages due to the lower workability in comparison to the mixtures containing higher fly ash content. This trend agrees with study by Singh et al (2020) [22] and Kassa et al (2019) [37] who reported a higher flexural strength at high fly ash content and low fibre reinforcement content.…”
Section: Effect Of Pet Fibre and Fly Ash On Composite Flexural Strengthsupporting
confidence: 93%
“…The results obtained for all levels of fly ash addition show decreased workability with increase in the fibre loading percentage. This conclusion has been reached in previous studies [32][33][34][35][36][37]. Adding incremental fibres into the concrete mixture enhances the internal friction between the concrete ingredients leading to reduced workability.…”
Section: Resultssupporting
confidence: 68%
“…In addition, Borg et al (2016) [10] noted a 0.5% to 8.5% strength reduction that on the addition of PET fibres in concrete due to the low elastic modulus of plastic fibres resulting in poor composite action [54], findings which have been supported by other researchers [55]. However, some studies show a slight improvement of compressive strength at 0.5% [44,50] and 1% [56] fibre dosage. It is worthwhile to note that in most of the studies that report an increase in compressive strength, short, smooth fibres were used, and hence fair compaction was achieved.…”
Section: Figure 10 Compressive Strength Results For the Different Sur...mentioning
confidence: 84%
“…In recent years, the construction industry has endeavored to solve environmental problems such as improperly disposed solid waste [8] where construction is one of the most complex jobs [9] so the need to recycle PET plastic to reduce these impacts by utilizing PET plastic as a mixture for concrete. By replacing or adding PET plastic into concrete is an innovation that can help to minimize the use of natural resources since concrete is one of the main materials in the construction world that is flexible, strong, and cost effective.…”
Section: Introductionmentioning
confidence: 99%